Behavioral Switching Model To Hybrid Learning Based on Push Pull Mooring Framework - Farliana, Nina; Setiaji, Khasan; Rusdarti, Rusdarti; Hardianto, Hanif (LPPM Undiksha, 2023)
The Covid-19 pandemic has resulted in a shift in hybrid-based learning. The purpose of this study is to analyze how the push-pull mooring effect is able to increase student behavior transition to hybrid learning during the Covid-19 pandemic. This study uses a quantitative approach. The research population is all active students of the Faculty of Economics. The sample used was 146 respondents, with non-probability sampling technique. The data collection technique was an online questionnaire method with an interval scale of agree (scale 7) to disagree (scale 1). Data analysis technique was based on Structural Equation Modeling Partial Least Square (SEM PLS) using WarpPLS 5.0 program. The results showed that the push effect, pull effect, mooring effect, decision self efficacy and motivation and intention switching had an effect on switching behavior. While the push and pull effects have no effect on switching behavior through motivation and intention to switch and decision self-efficacy, in contrast to the mooring effect which has a significant effect. The findings of this study are that hybrid learning has not been able to improve student performance than offline learning, so the student behavior to switch to hybrid learning still needs to be improved.